Survival and cause-specific mortality of European wildcat (Felis silvestris) across Europe. (September 2021) - Bastianelli, Matteo Luca; Premier, Joseph; Herrmann, Mathias; Anile, Stefano; Monterroso, Pedro; Kuemmerle, Tobias; Dormann, Carsten F.; Streif, Sabrina; Jerosch, Saskia; Götz, Malte; Simon, Olaf; Moleón, Marcos; et al.
Abstract: Humans have transformed most landscapes across the globe, forcing other species to adapt in order to persist in increasingly anthropogenic landscapes. Wide-ranging solitary species, such as wild felids, struggle particularly in such landscapes. Conservation planning and management for their long-term persistence critically depends on understanding what determine survival and what are the main mortality risks. We carried out the first study on annual survival and cause-specific mortality of the European wildcat with a large and unique dataset of 211 tracked individuals from 22 study areas across Europe. Furthermore, we tested the effect of environmental and human disturbance variables on the survival probability. Our results show that mortalities were mainly human-caused, with roadkill and poaching representing 57% and 22% of the total annual mortality, respectively. The annual survival probability of wildcat was 0.92 (95% CI = 0.87–0.98) for females and 0.84 (95% CI = 0.75–0.94) for males. Road density strongly impacted wildcat annual survival, whereby an increase in the road density of motorways and primary roads by 1 km/km 2 in wildcat home-ranges increased mortality risk ninefold. Low-traffic roads, such as secondary and tertiary roads, did not significantly affect wildcat's annual survival. Our results deliver key input parameters for population viability analyses, provide planning-relevant information to maintain subcritical road densities in key wildcat habitats, and identify conditions under which wildcat-proof fences and wildlife crossing structures should be installed to decrease wildcat mortality. Highlights: Understanding survival is crucial for effective species conservation. We studied survival and cause-specific mortality of European wildcat across Europe. 83% of wildcat annual mortality was caused by humans. Roadkill was the main source of mortality for the wildcat in Europe. Survival decreased with increasing density of high-traffic roads.